Novel microencapsulated probiotic blend for use in metabolic syndrome: design and in-vivo analysis. (12th November 2018) - Iqbal, Umar Haris; Westfall, Susan; Prakash, Satya
Abstract: The increasing prevalence of the metabolic syndrome has made it a medical issue that currently affects 1 in 5 Canadians. The metabolic syndrome is defined by risk factors that predispose an individual to diabetes and cardiovascular disease. Current forms of interventions have been inadequate as substantiated by the fact that the prevalence of metabolic syndrome has not reduced over the years. The objective of this study was to investigate the therapeutic benefits of a novel microencapsulated probiotic blend in treating the metabolic syndrome. Three probiotic strains were microencapsulated into alginate-polylysine-alginate (APA) microcapsules: L. rhamnosus NCIMB 6375, L. plantarum NCIMB 8826 and L. fermentum NCIMB 5221. From the results, it was observed that the microencapsulated probiotic blend significantly reduced serum total cholesterol, LDL cholesterol and triglyceride levels (reducing from 516 mg/dL to 379 mg/dL, 314 mg/dL to 231 mg/dL and 580 mg/dL to 270 mg/dL, respectively). In addition, the administration of the microencapsulated probiotic blend was found to favourably influence the gut microbiota, decreasing Firmicutes levels and increasing Bacteroidetes levels. Overall, this work demonstrates the potential a microencapsulated probiotic blend could have in targeting multiple risk factors of the metabolic syndrome; however, greater research is still needed.